The Influence of Capital Structure, Liquidity, Solvency and Firm Growth on the Company’s Financial Distress That is Mediated by Profitability (A Study on 12 Indonesia General Insurance Companies Listed on the Indonesian Stock Exchange 2015-2020) - Rismala, Lina Indra; Holiawati, Holiawati; Sunardi, Nardi (ADPEBI, 2022)
This research aims to analyze the influence of capital structure, liquidity, solvency and firm growth on the company’s financial distress that is mediated by profitability in 12 (twelve) general insurance companies listed in the Indonesia Stock Exchange 2015-2020. It applies an associative quantitative research method using secondary data of the published Annual Report of the Indonesian general insurance companies during the above mentioned period, which therefore are determined as research samples and are made by the purposive sampling method. The panel data regression analysis was carried out by applying the EViews v9.0 software supported by Microsoft Excel usage. The data analysis uses the estimation method of multiple linear regression models with descriptive analysis. Classical assumption test consists of normality, autocorrelation, multi-collinearity and heteroscedasticity. Thereafter it is followed by hypothesis testing (t test, F test), detection of mediation effect and path analysis through the Sobel test. The results of this study provide information that all relevant companies as mentioned are all having the high probability of risking financial distress. Capital structure and solvency have immediate affect on profitability, whereas liquidity and firm growth does not, simultaneously the combination of all does have. In regard to financial distress, then capital structure and profitability does have affect, whereas liquidity, solvency and firm growth does not, but again the combination of all will have affect. Profitability mediates the capital structure that in turn influences financial distress, but this does not necessarily mediate liquidity, solvency and firm growth. Profitability however does affect on financial distress